Hubungan Ketergantungan Internet dengan gangguan Interaksi Sosial pada Remaja - Zudatul Diana; Siti Juwariyah; Mamat Supriyono (Pusat Riset dan Inovasi Nasional, 2023)
The internet is now a basic human need for carrying out human activities. The existence of the internet makes it easy for humans to carry out their activities, both physical and non-physical. People become dependent on the internet because of the convenience it offers. Internet dependence can cause problems in adolescent life, such as reduced interest in daily life and social interaction problems. This study aimed to determine the relationship between internet dependence and social interaction in adolescents. The method used in this study was a correlational descriptive study design, with the approach used being cross-sectional. With a total population of 307 high school students between the ages of 15 and 17, the sample in this study used the Cohen, Manion, and Morisso sampling percentage reference, yielding 143 samples at a 90% confidence level and a p-value of 0.1. This research uses a probability sampling technique using simple random sampling; the data is then analyzed using the chi-square test. The questionnaire used in this study is the Internet Addiction Disorder Questionnaire. The results showed that 87.4% of respondents experienced internet dependence, and only 12.6% of teenagers who did not experience internet dependence experienced social interactions between adolescents with parents (p 0.092), peers (p 0.042), and at school (p 0.018), but not social interaction in the community (p 0.013). Suggestions for further research include paying attention to other factors that influence social interaction besides the intensity of playing on the internet. Besides that, it can also expand the population and increase the sample size so that the research generalization becomes broader than this current study.